2021
DOI: 10.1021/acs.inorgchem.1c02236
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of 5f Orbitals in the Covalent Bonding between the Uranyl Ion and Trialkyl Phosphine Oxide: Unraveled by Oxygen K-Edge X-ray Absorption Spectroscopy and Density Functional Theory

Abstract: Monodentate organophosphorus ligands have been used for the extraction of the uranyl ion (UO 2 2+) for over half a century and have exhibited exceptional extractability and selectivity toward the uranyl ion due to the presence of the phosphoryl group (OP). Tributyl phosphate (TBP) is the extractant of the world-renowned PUREX process, which selectively recovers uranium from spent nuclear fuel. Trialkyl phosphine oxide (TRPO) shows extractability toward the uranyl ion that far exceeds that for other metal ions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 102 publications
0
25
0
Order By: Relevance
“…Actinide-ligand covalency has been studied using a variety of experimental techniques, including X-ray absorption spectroscopy, X-ray crystallography, NMR spectroscopy, EPR spectroscopy, and optical spectroscopy. With respect to optical spectroscopy, complexes with the 5f 1 electronic configuration have proven to be especially useful. , The lack of electron–electron repulsion in this configuration allows the spin–orbit coupling to be treated in a relatively straightforward manner. , For example, in 2013, we reported a comprehensive bonding analysis of a series of O h -symmetric 5f 1 complexes, including [U V (CH 2 SiMe 3 ) 6 ] − , [U V (O t Bu) 6 ] − , and [U V X 6 ] − (X = F, Cl, Br), which permitted an estimate of the strengths of the ligand–f-orbital interactions. More recently, Liddle and co-workers analyzed the optical and EPR spectra of the C 3v -symmetric U­(V) nitride, [U V (Tren TIPS )­(N)] − (Tren TIPS = N (CH 2 CH 2 N Si i Pr 3 ) 3 ), and extracted the corresponding crystal field splitting parameters .…”
Section: Introductionmentioning
confidence: 99%
“…Actinide-ligand covalency has been studied using a variety of experimental techniques, including X-ray absorption spectroscopy, X-ray crystallography, NMR spectroscopy, EPR spectroscopy, and optical spectroscopy. With respect to optical spectroscopy, complexes with the 5f 1 electronic configuration have proven to be especially useful. , The lack of electron–electron repulsion in this configuration allows the spin–orbit coupling to be treated in a relatively straightforward manner. , For example, in 2013, we reported a comprehensive bonding analysis of a series of O h -symmetric 5f 1 complexes, including [U V (CH 2 SiMe 3 ) 6 ] − , [U V (O t Bu) 6 ] − , and [U V X 6 ] − (X = F, Cl, Br), which permitted an estimate of the strengths of the ligand–f-orbital interactions. More recently, Liddle and co-workers analyzed the optical and EPR spectra of the C 3v -symmetric U­(V) nitride, [U V (Tren TIPS )­(N)] − (Tren TIPS = N (CH 2 CH 2 N Si i Pr 3 ) 3 ), and extracted the corresponding crystal field splitting parameters .…”
Section: Introductionmentioning
confidence: 99%
“…Together, these results indicate that electrochemically generated PO Cb 2− selectively captures UO 2 2+ from a mixed alkali, lanthanide, and actinide aqueous phase. While the nature of this selectivity remains under investigation, we suspect that optimal covalent bonding interactions between the PO units and the U center – very recently investigated in the PUREX context 29,30 – are likely at play.…”
Section: Resultsmentioning
confidence: 93%
“…4 For instance, only very recently have TRPO derivatives been identified to have excellent binding to uranyl (UO 2 2+ ) due to optimized covalency and the involvement of the U 5f orbitals. 5 We have previously shown that redox-switchable ortho-closocarboranes bearing coordinating phosphine oxide donors, 1,2-(Ph 2 PO) 2 -1,2-C 2 B 10 H 10 ( PO Cb), could be electrochemically reduced to the nido-carborane, PO Cb 2− , an efficient extractant for biphasic UO 2 2+ capture (Figure 1a). Release of UO product back to its closo ( PO Cb) form.…”
Section: ■ Introductionmentioning
confidence: 97%
“…In most cases, however, phosphine oxide-based extractants are most effective at capturing actinides, but there remains a surprising knowledge gap in the literature between structure–activity relationships of the ligands and corresponding UO 2 2+ extraction properties . For instance, only very recently have TRPO derivatives been identified to have excellent binding to uranyl (UO 2 2+ ) due to optimized covalency and the involvement of the U 5f orbitals …”
Section: Introductionmentioning
confidence: 99%